Transmisi Gelombang Melalui Pemecah Gelombang Susunan Pipa Horizontal - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
A horizontal piped breakwater is a horizontal pipe pilled construction for reduction of the wave energy. This structure may be used to prevent harbors and beaches from wave attacks, especially during the storm condition. The aim of this research was to investigate the transmission, reflection and dissipation of the wave energy when propagating wave through a horizontal piped breakwater. Physical model tests were conducted at IUC-ES hydraulic laboratory. Variations of pipe diameter, wave height and wave period were that investigation, whilst regular wave was used in the attack wave. The result of the investigation shows that the transmitted and reflected wave height is influenced by the relative dimension of the horizontal pipd breakwater. The longer is the pipe, the smaller wave transmission and the greater wave reflection results. Key words: transmission, reflection, dissipation.